Introduction to pattern recognition a MATLAB approach - Theodoridis, Sergios 1951- (Academic, 2010)
An accompanying manual to Theodoridis/Koutroumbas, Pattern Recognition, that includes Matlab code of the most common methods and algorithms in the book, together with a descriptive summary and solved examples, and including real-life data sets in imaging and audio recognition
Includes bibliographical references and index
Keywords: MATLAB.; Pattern perception; Pattern recognition systems; Online-Publikation; MATLAB; Mustererkennung